Fine ware at Schedia (Western Delta, Egypt): A Choice of Identity? - Martin, Archer (Rei Cretariae Romanae Fautorum Acta, 2015)
The concept a Roman fine-ware boom in the Augustan Tiberian period is familiar. People both in the East and the West wished to present themselves at table in the Roman fashion, by using either Italian sigillata or wares that adopted the repertoire of Italian sigillata. The latter might be newly created wares (such as Gaulish sigillata or Eastern sigillata B) or existing ones that underwent a profound renewal (such as Eastern sigillata A). After this time of unity, each ware developed on its own.